ENTREPRENEUSHIP TRAINING NEED ANALYSIS AMONG URBAN LOW INCOME TEENAGERS - Siti Fardaniah Abdul Aziz (Journal of Islamic, Social, Economics and Development, 2018)
Teenagers living in the area of citizen housing project (PPR) Kuala Lumpur is categorized as urban low income teenagers; in which, their family average income is less than RM940 per month. Previous studies have shown that this community is experiencing economic pressures that plunge them into other problems such as social, crime, drug and fights. Volume: 3 Issue: 11 [June, 2018] pp. 96 - 105] Journal of Islamic, Social, Economics and Development eISSN: 0128-1755 Journal website: www.jised.com m97 Therefore, the community needs to be helped so that they are not in constant economic pressure. One of the efforts that can be done to assist the community is to provide human development programs; for example, Entrepreneurial Skills Programs so that they can choose to be entrepreneur and thus increase their household income. Hence, a training need analysis was conducted to determine the level of knowledge, skills and entrepreneurship interests among 92 teenagers at PPR Pantai Dalam and Desa Rejang, Kuala Lumpur. Findings show that only 41.3% of these teenagers passed an informal quiz on entrepreneurial knowledge. In addition, based on self-perception, majority of them perceived that the level of knowledge, skills and interest in entrepreneurship was only at a moderate level. This suggests that there is a need to increase their level of knowledge, skills, and interests in the field of entrepreneurship through appropriate training program.